Peran Artificial Intelligence (AI) Dalam ProsesPembelajaran Mahasiswa PGMI Di STITAl-Bukhary LabuhanbatuSumatera Utara - Irpan Siregar Irpan Siregar; Suryatik; Muhammad Zulham Munthe (Jurnal Zeniusi, 2024)
Information technology has become an important part of human life, especially with the rapid development in the field of artificial intelligence (AI). AI plays a significant role in improving the effectiveness and efficiency of learning, especially in higher educationenvironments. This study aims to explore the role of AI in students' lives, focusing on the application of AI in education and its impact on students' learning experiences. This study uses a quantitative descriptive method with data collection through a survey of 30 Elementary Madrasah Teacher Education (PGMI) students at STITA Labuhanbatu. The survey results show that the majority of students have a good understanding of AI and a positive perspective on its influence on learning. AI has been shown to improve personalization in learning, assist academic administration, and prepare students for an increasingly digital workforce. However, this study also identifiednegative impacts, such as the potential for declining student literacy and the risk of technology addiction. Therefore, it is important to improve digital literacy and education about AI so that students can utilize this technology optimally and responsibly.